cDNA cloning of the hepatocyte canalicular isoform of the multidrug resistance protein, cMrp, reveals a novel conjugate export pump deficient in hyperbilirubinemic mutant rats - König, Jörg; et al. (Journal of Biological Chemistry, 1996)
ATP-dependent transport of glutathione and glucuronate conjugates from hepatocytes into bile is mediated by a distinct member of the ATP-binding cassette superfamily. We have cloned and sequenced the canalicular isoform of the multidrug resistance protein from rat liver, and termed it cMrp. This membrane glycoprotein is composed of 1541 amino acids with an identity of 47.8% with the human multidrug resistance protein (MRP) and of 41.9% with the yeast cadmium factor (YCF1). The carboxyl-terminal 130 amino acids of the human hepatocyte canalicular isoform of MRP (cMRP) were 80.2% identical with rat cMrp. cMrp was not expressed in the liver of two mutant rat strains, the Eisai hyperbilirubinemic rat and the GY/TR- mutant, which are deficient in the ATP-dependent transport of conjugates across the canalicular membrane. Immunoblotting using an antibody raised against the carboxyl terminus of cMrp detected the glycoprotein of about 190 kDa only in the canalicular membrane from normal liver. Double immunofluorescence and confocal laser scanning microscopy localized cMrp exclusively to the canalicular membrane domain of hepatocytes and demonstrated its loss in the hyperbilirubinemic mutant rat. The results identify cMrp as a canalicular transport protein with a novel sequence and with a function similar to the one of the MRP.
Created from Fastlane, Scopus look-up